Dystocia due to Dicephalic Parapagus Tetrabrachius Tetrapus Twin Monster in a Cow: A case Report - Pansuriya, Dhaval; Patel, Chirag I.; Patel, Hardik; Bhalodia, Sanjay (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Monsters are developmental abnormalities that distort organs and body systems. Developmental abnormalities of the ovum, embryo or fetus occur in all species of domestic animals. Monstrosity is a disturbance of the development that involves various organs and systems which can cause great distortion of the individual (Vegad, 2007). The monstrosities are associated with either infectious diseases or congenital disabilities (Arthur et al., 2001), which may or may not interfere with birth. Abnormal duplication and/or disruption of the inner cell mass in an embryo give rise to congenital fetal abnormalities with partial duplication of body structures. Duplication of cranial portion of the fetus is more common than caudal portion (Roberts, 2004). It is important to know various types of monsters in animals that usually cause dystocia, which cannot be easily delivered and require a Caesarean section or a fetotomy mostly (Patil et al., 2004; Sharma, 2006). The incidence of fetal monsters, though rare, have been reported in cows (Khasatiya et al., 2009; Jerome et al., 2010; Ravikumar et al., 2012), in buffaloes (Dhami et al., 2000; Prasad et al., 2006; Sharma et al., 2010) and in goats (Pandit et al., 1994). This communication reports a rare case of conjoined twin monster (Dicephalus Paracopagus Tetrabrachius Tetrapus Dicaudatus) in a pluriparous crossbred cow.